The honey-don't list [compact disc, unabridged] - Lauren, Christina (Simon & Schuster Audio, 2020)
Carey Douglas has worked for home remodeling and design gurus Melissa and Rusty Tripp for nearly a decade. Carey started in their first store at sixteen, and, more than anyone would suspect, has helped them build an empire. With a new show and a book about to launch, the Tripps are on the verge of superstardom. There's only one problem: America's favorite couple can't stand each other. James McCann, MIT graduate and engineering genius, was originally hired as a structural engineer, but the job isn't all he thought it'd be. The last straw? Both he and Carey must go on book tour with the Tripps and keep the wheels from falling off the proverbial bus. Unfortunately, neither of them is in any position to quit. While road-tripping with the Tripps up the West Coast, Carey and James vow to work together to keep their bosses' secrets hidden, and their own jobs secure. But if they stop playing along, and start playing for keeps, they may have the chance to build something beautiful together.